(untitled) (Research, Society and Development, 2022)
Introduction: The neonatal intensive unit is a place for patients at risk, which demands attention from the team and requires adequate conditions to ensure safety, especially concerning neonatal acoustic comfort. OBJECTIVE: Identify environmental noise level in neonatal intensive care units and verify their compliance with the recommendations. Methods: This integrative review was conducted based on a question: What are the levels of environmental noise found in neonatal intensive care units? Data were collected on portal Biblioteca Virtual em Saúde and PubMed, “noise” and “neonatal intensive care” were the keywords and articles published from January 2015 to December 2021 were included in the study. A total of 44 articles were selected. Results: All noise measurements showed sound pressure levels above those recommended by the American Academy of Pediatrics. Continued education was cited as the best strategy for noise reduction, and should include the care team and parents, allowing for the implementation of more permanent changes. Conclusion: It is necessary to give importance to noise control and solutions to avoid it, and to spread awareness that the professional team is also a noise-producing agent. Research should be encouraged to reduce noise and implement strategies for reducing it.